Preliminary Investigation on Spider Fauna (Arachnida: Araneae) of Nauradehi Wildlife Sanctuary, Madhya Pradesh, India - Patil, Sachin R.; Bhandari, Rita; Chandra, Kailash (Indian Forester, 2016)
The present paper is based on preliminary investigation of the spider fauna of Nauradehi Wildlife Sanctuary spread in Sagar, Narsinghpur and Damoh districts of Madhya Pradesh, India. There is no report on the spider fauna from this sanctuary. Altogether 51 species of spiders belonging to 25 genera under 12 families from the sanctuary are studied and reported for the first time in the present paper.